2000
DOI: 10.1073/pnas.090464197
|View full text |Cite
|
Sign up to set email alerts
|

Cortical cell death induced by IL-1 is mediated via actions in the hypothalamus of the rat

Abstract: The cytokine IL-1 mediates diverse forms of neurodegeneration, but its mechanism of action is unknown. We have demonstrated previously that exogenous and endogenous IL-1 acts specifically in the rat striatum to dramatically enhance ischemic and excitotoxic brain damage and cause extensive cortical injury. Here we tested the hypothesis that this distant effect of IL-1 is mediated through polysynaptic striatal outputs to the cortex via the hypothalamus. We show that IL-1␤ injected into the rat striatum with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 43 publications
1
40
1
3
Order By: Relevance
“…The fact that ionotropic glutamate receptor antagonism prevents the potentiation of hypoxic neuronal injury by IL-1␤ indicates that these changes are not merely correlative but represent the cause of injury. A link between glutamate receptormediated injury and IL-1␤ is further strengthened by in vivo evidence showing that intrastriatal injection of IL-1␤ enhances excitotoxic neuronal injury (Lawrence et al, 1998;Stroemer and Rothwell, 1998;Allan et al, 2000), whereas striatal and hippocampal neuronal injury induced by direct NMDA receptor 4 except supernatant was collected after 120 min of oxygen deprivation to measure accumulation of glutamate in the bathing medium via HPLC. Data are expressed as the mean Ϯ SEM glutamate accumulation in micromolar (n ϭ 4 -5 cultures pooled from 2 different experiments).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that ionotropic glutamate receptor antagonism prevents the potentiation of hypoxic neuronal injury by IL-1␤ indicates that these changes are not merely correlative but represent the cause of injury. A link between glutamate receptormediated injury and IL-1␤ is further strengthened by in vivo evidence showing that intrastriatal injection of IL-1␤ enhances excitotoxic neuronal injury (Lawrence et al, 1998;Stroemer and Rothwell, 1998;Allan et al, 2000), whereas striatal and hippocampal neuronal injury induced by direct NMDA receptor 4 except supernatant was collected after 120 min of oxygen deprivation to measure accumulation of glutamate in the bathing medium via HPLC. Data are expressed as the mean Ϯ SEM glutamate accumulation in micromolar (n ϭ 4 -5 cultures pooled from 2 different experiments).…”
Section: Discussionmentioning
confidence: 99%
“…19 Increased NO release from activated leukocytes and astrocytes leads to the production of peroxynitrite, which can irreversibly damage lipids and proteins causing cell death, 18 and extensive neocortical injury occurs as a consequence of enhanced glutamate excitotoxicity after IL-1␤ injection into the striatum or hypothalamus. 20 These are not separate pathophysiological mechanisms, because NO can enhance glutamate excitotoxicity. 16 Although iNOS Ϫ/Ϫ mice have lower infarct volumes compared with WT, the neuroprotection is only partially observed in the neocortex.…”
Section: Discussionmentioning
confidence: 99%
“…Both IL-1 ligands (IL-1␣ and IL-1␤) are produced rapidly in the brains of rodents exposed to cerebral ischemia (Wang et al, 1994;Hillhouse et al, 1998;Zhang et al, 1998), and recombinant IL-1␤ administered intracerebroventricularly, or directly into the brain, enhances ischemic and other forms of injury (Yamasaki et al, 1995;Loddick and Rothwell, 1996;Lawrence et al, 1998;Stroemer and Rothwell, 1998;Allan et al, 2000). Conversely, blocking IL-1 actions, by administration of the naturally occurring and selective IL-1 receptor antagonist (IL-1ra), markedly reduces neuronal loss and inflammation induced by a variety of experimental brain insults (Relton and Rothwell, 1992;Lin et al, 1995;Betz et al, 1995;Garcia et al, 1995;Yamasaki et al, 1995;Loddick and Rothwell, 1996;Stroemer and Rothwell, 1998;Yang et al, 1998).…”
Section: Abstract: Interleukin-1; Cytokines; Stroke; Brain; Knock-oumentioning
confidence: 99%
“…Both cytokines are induced in response to cerebral ischemia (Touzani et al, 1999) or excitotoxicity, and central administration of IL-1␤ exacerbates damage (Allan et al, , 2000Lawrence et al, 1998). Yamasaki et al (1995) reported that intracerebroventricular injection of neutralizing anti-IL-1␤ antibody to rats reduces ischemic brain damage, implicating IL-1␤ as the major mediator of injury.…”
Section: Abstract: Interleukin-1; Cytokines; Stroke; Brain; Knock-oumentioning
confidence: 99%